Tick Size Implementation of Kompas 100 Index at Indonesia Stock Exchange - Hamid, Agustini (Bina Nusantara University, 2016)
Tick Mechanism was included in market microstructure. It studied the process which investorsâ latent demands were ultimately translated into prices and volumes. This research reviewed the theoretical, empirical, and experimental literature on market microstructure relating to return, volatility, and liquidity after implementation of new tick size in Indonesia Stock Exchange (IDX). The study took a sample of Kompas 100 index because it was represented all level of tick size at IDX. The data were analyzed using differences test with analysis tools e-views. Using Wilcoxon Signed Rank Test, there were not significance difference of volatility, return, and liquidity after the implementation of new tick size. The difference of implementation new tick size were contrary results that old tick size has a positive value to return and liquidity while it was negative for volatility. It means that increasing of liquidity and return have the impact to volatility. While the implementation of new tick size has the negative impact to return, liquidity, and volatility.